2013
DOI: 10.22499/2.6301.015
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to atmospheric physical parameterisations aimed at improving SST simulations in the ACCESS coupled model

Abstract: The Australian Community Climate and Earth System Simulator (ACCESS) has been developed at the Centre for Australian Weather and Climate Research. It is a coupled modeling system consisting of ocean, atmosphere and land surface. The ACCESS atmospheric component is the UK Met Office Unified Model (UM). The initial results from the ACCESS coupled model had significant errors in the sea surface temperature (SST). It has been identified that the SST bias is largely due to errors in the representation of clouds. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…This has been demonstrated by Fig. 6 in Sun et al () in which we have shown that the implementation of a new ice cloud fraction scheme (Franklin et al , ) leads to an increase of high‐level cloud fraction in the ACCESS model and results in a reduction of SO warm bias (Fig. 6c vs. 6b in Sun et al, ).…”
Section: Experiments With the Access Modelsupporting
confidence: 69%
See 2 more Smart Citations
“…This has been demonstrated by Fig. 6 in Sun et al () in which we have shown that the implementation of a new ice cloud fraction scheme (Franklin et al , ) leads to an increase of high‐level cloud fraction in the ACCESS model and results in a reduction of SO warm bias (Fig. 6c vs. 6b in Sun et al, ).…”
Section: Experiments With the Access Modelsupporting
confidence: 69%
“… Land surface scheme: The Community Atmosphere Biosphere Land Exchange (CABLE: Kowalczyk et al , ) replaces the Met Office's Surface Exchange Scheme (MOSES). Radiation: The triple‐cloud scheme (Shonk et al , ) is used to represent the effect of cloud horizontal inhomogeneity on the radiation. Clouds: A modified ice cloud fraction parametrization by Franklin et al () and the area cloud fraction correction scheme described by Boutle and Morcrette () have been used. Boundary layer: A modified air–sea flux exchange scheme (Sun et al , ) has been used. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of this scheme and its evaluation within the ACCESS model are provided by Sun et al (2013). This implementation differs from the simpler scaling scheme implemented in GA1.0 to account for cloud inhomogeneity (Hewitt et al 2011).…”
Section: Access13mentioning
confidence: 99%
“…A full evaluation of results presented by Sun et al [14]. Only surface radiation and sea surface temperature (SST) are shown here due to the limit of page length limit.…”
Section: Resultsmentioning
confidence: 99%